The Impact of Disclosure on Health and Related Outcomes in Human Immunodeficiency Virus-Infected Children: A Literature Review - Odiachi, Angela (Frontiers in Public Health, 2017)
This review explores the association between pediatric HIV disclosure and health and related outcomes among children living with HIV. A multi-stage process was used to search for relevant articles on the ISI Social Science database. Fifteen articles met the inclusion criteria. Five major outcomes emerged from children’s knowledge of their HIV-seropositive status: physical/physiological outcomes; adherence to antiretroviral therapy; self-esteem, mental, emotional and other psychosocial outcomes; sexual and reproductive health, including HIV prevention outcomes; and disclosure of status by the children. Disclosure of a child’s HIV status to the child has value in terms of positive health outcomes for the child, such as better adherence and slower disease progression - albeit the different studies did not always reach the same conclusions, and some suggest negative health outcomes, such as increased psychiatric hospitalization. Yet, there does not seem to be a systematic or coherent system for child disclosure. One recommendation from this review, therefore, is for government and program policies and guidelines that will promote child HIV disclosure in order to address the current low rates of disclosure in sub Saharan Africa. More rigorous studies on the outcomes of disclosure, with larger sample sizes, and in sub-Saharan Africa, are also needed.